PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASI PELAJAR ISLAM INDONESIA - Khusnul Khuluq Febrianto; Ghozali Rusyid Affandi (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2023)
Organization is a container for humans who have the same goal. The organization in it has the most important aspect, namely human resources, without humans the organization will not walk alone towards its goals. Organizational goals, especially non-profit organizations, will require people who have a strong desire to run the organization. This strong desire to organize is called organizational commitment. The research method used is a quantitative method, a method that measures using numbers. The quantitative approach used is correlation in knowing the relationship of the independent variable to the dependent variable. The independent variables in this study are leadership style and organizational culture. The dependent variable in this study is organizational commitment. The findings in this study were that there was only 1 female respondent in the low category of organizational commitment. There are 47% of respondents in the moderate category, 23% of men and 25% of women. In the high category, there were 52% of respondents, 27% of men and 25% of women. The conclusion from this study is that transformational leadership style has a positive effect on organizational commitment, organizational culture has a positive effect on organizational commitment, transformational leadership style and organizational culture together have a positive effect on organizational commitment